Hannah Arendt and political theory : challenging the tradition - Buckler, Steve, 1960- (Edinburgh University Press, 2011)
Hannah Arendt's work has been noted for its unorthodox and eclectic style. Steve Buckler now shows that her unusual approach reflects a consistent and distinctive conception of, and way of doing, political theory. Through close readings of her works, Buckler argues that Arendt's work is an important and challenging alternative to the more orthodox methods characteristic of both analytic and post-analytic political theory. Key Features. Discusses Arendt's key works - The Origins of Totalitarianism, The Human Condition and On Revolution - alongside her less well known and posthumously published writing Shows how Arendt framed problems with respect to specific concerns in the modern polity and democratic culture Considers Arendt's views on totalitarianism, political theory, the concept of action, revolutions, political ethics, and the role of the thinker